DEADJEKTIVA NOMINA OLEH SUFIKS –SA, –MI, DAN –ME - Endang Poerbowati (Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract. This paper discusses nouns derived from adjectives, especially adjectival nouns formed through the additional of suffies –sa, -mi, and –me. Not only do the adjectives undergo a process of class word shifts, but also they experience the change in meaning. There are interesting form changes undergoing by adjectival nouns (nouns derived from adjectives) which are diference from their roots or stems. Some derivational affixes attachto the roots and stems of the adjectives and produce nouns and new meanings. Deadjectival nouns can be formed by adding suffixes –sa, -me, and –mi. There are some adjectives that can be formed into nouns by adding suffix –sa. They are –I, adjective –na, compound adjectives, and borrowing adjectives of foreign languages. Suffix –sa marks a definite change from an adjective to a noun. It is found only one occurance of the process of deadjectival noun by adding suffix –mi, that is the adjective –I. Suffix –mi deals with expression of senses or perceptive organs. Lastly, there is only one occurance of deadjectival noun process by adding –me, that is adjective –I. The meaning of the suffix implies a rank and tendency in its use. Keywords: suffix –sa, suffix –mi, suffix –me, deadjectival, morphological process